On Practices of Images and Measures of Practice - Jane Birkin; Jussi Parikka (Media Theory)
This conversation between Jane Birkin and Jussi Parikka picks up on two recently published books, Birkin’s Archive, Photography and the Language of Administration (Amsterdam University Press 2021) and Parikka’s co-edited Photography off the Scale (Edinburgh University Press, 2021, with Tomáš Dvo?ák). The conversation focuses on some of the media theoretical undercurrents of their two books that feature the photographic image as a central part of both their interests, while also shifting to different aspects of institutional practices of images, including questions of logistics of order and enumeration.